The sociopolitics of sport, physical education, and school health in the United States. Issue 4 (1st October 2016) - Ressler, James D.; Richards, K. Andrew R.; Wright, Paul M.
ABSTRACT: Evidence from global sources indicate that physical education (PE) has an integral role to play in the development of behaviours supporting lifetime physical activity. However, PE programmes in many countries fall short of accomplishing this charge. The marginality of PE in comparison to school-based athletic programmes, and inter-role conflict arising from concurrent performance of teaching and coaching roles contribute to this phenomenon. Grounded in role socialisation theory and drawing primarily from the United States context, we explore the social construction of PE teaching and athletic coaching roles in school environments. Different priorities and time demands can lead to conflict, and teachers/coaches often prioritise the role for which they are rewarded and held most accountable. These reward and accountability structures favour coaching in many schools, leading teachers/coaches to focus on coaching to the detriment of their teaching performance. Formal accountability and reward structures are reinforced by administrators, colleagues, children and community members who praise coaching prowess, but fail to acknowledge successes in teaching environments. Since only a small percentage of school children engage in interscholastic athletics, the complex relationship between teaching and coaching can inhibit physical activity and public health agendas that seek to enhance children's health through school-based programming. The content of PE at the secondary level, which replicates team sport environments and reinforces athletic achievement, also marginalises children who are not interested in traditional forms of sport. It is against this backdrop that we discuss opportunities and challenges for the future of PE as a public health intervention.